Trying to Live With Pumping: Expressing Milk for Preterm or Small for Gestational Age Infants. Issue 2 (March 2016) - Ikonen, Riikka; Paavilainen, Eija; Kaunonen, Marja
Abstract: Purpose: To describe mothers' experiences with expressing breast milk for preterm or SGA infants. Study Design and Methods: This is a descriptive qualitative study involving 130 mothers of preterm or SGA infants admitted to a neonatal intensive care unit. Data were collected in collaboration with two Finnish peer support associations. An Internet-based questionnaire with open-ended questions was administered to respondents. Responses were analyzed with inductive content analysis. Results: Mothers had to try to manage daily life and breast pumping. The combination of preterm birth and separation from the hospitalized infants served simultaneously as motivating factors and obstacles. Mothers tried to look beyond the unnatural and difficult process of milk expression, looking forward to eventual breastfeeding. Concerns about time and scheduling, equipment, environment, and sufficient milk supply were prevalent, as well as feelings of unfamiliarity, difficulty, frustration, and loneliness. Clinical Implications: Expressing breast milk should be considered as a helpful factor for preterm or SGA infants' mothers. Separation between mother and infant should be avoided. Mothers need adequate equipment and a private space for expressing milk, in addition to assistance with their daily routines. For mothers to successfully manage expression, they also require an environment that fosters a sense of caring, normality, and hope, as well as frequent care for their emotional needs. Abstract : Concern about infant feeding is a common problem reported by mothers of preterm babies admitted to neonatal intensive care units. This study explores the experiences of mothers of preterm babies as they faced the challenges of pumping breast milk to provide the best nutrition for their baby and maintain their ability to breastfeed once the baby was able.